Ranking The Strictness Level Of Sharia Stock Screening Standards: A Comparative Analysis Of Global Sharia Stock Indices - Fatoni, Ahmad; Utami, Kurnia Dwi Sari; Najmudin, Najmudin; Fakhrudin, Muhamad (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
This study aims to rank the level of strictness in Sharia stock screening standards across five major indices DJIM, MSCI Islamic, FTSE Shariah, KLSI, and ISSI. The research uses a qualitative-comparative analysis with a weighted scoring approach based on five key indicators: debt ratio, non-halal income tolerance, prohibited sectors, purification mechanisms, and technical screening methods. The results show that DJIM and MSCI fall into the very strict category, FTSE and KLSI are moderate, while ISSI is categorized as lenient. This variation provides important insights for investors and regulators in assessing how far an index reflects Sharia compliance and prudential standards.